Starptautisko un Eiropas Savienības tiesību normu piemērošana Latvijā - teorētiskie aspekti - Pļaviņa, Katrīne (Latvijas Universitāte, 2011)
Pirmajās divās darba nodaļās autore analizē katra starptautiskā avota normu vienotību vai šķirtību ar Latvijas tiesību sistēmu un secina, ka starptautisko tiesību un Latvijas tiesību sistēmas ir vienota sistēma. Tādējādi starptautisko un Latvijas tiesību normu pretrunas jārisina, pirmkārt, normas pārinterpretējot un atrodot harmoniju, otrkārt, nosakot starptautisko tiesību normu vietu Latvijas tiesību normu juridiskā spēka hierarhijā un, treškārt, starptautisko tiesību normu piemērojot prioritāri pār Latvijas tiesību normām.  Otrajās divās darba nodaļās autore noskaidro, ka no Latvijas skatpunkta ES tiesību sistēma ir Latvijas tiesību sistēmas daļa, kas ieviesta ar starptautisku līgumu. Savas izcelsmes dēļ ES tieši iedarbīgas normas piemēro saskaņā ar starptautisko tiesību normām piemērotajiem soļiem. Savukārt tieši neiedarbīgas normas ES piemēro atbilstoši EST judikatūrai, t.i., atbilstoši tā Latvijas akta, ar kuru tās ieviestas, vietai juridiskā spēka hierarhijā. Saskaņā ar EST judikatūru ES normas, kurām piemīt vienāds juridisks spēks ar Latvijas normām, piemēro prioritāri.

In the first two chapters of the thesis the author analyses unity or distinction of every source of international law with the legal system of Latvia and concludes that the legal systems of international law and Latvia are united. Thus, one solves contradictions of legal norms of these legal systems, firstly, by re-interpretation in search of a harmonious solution, secondly, by determining the place of the legal norms of international law within the legal hierarchy of Latvia’s norms, and, thirdly, by applying norms of international law as primary to the legal norms of Latvia. In the second two chapters of the work the author establishes that, according to Latvia, the legal system of the European Union is a part of its legal system, which has been implemented by an international treaty. Due to its origin, effective European Union norms are applied directly according to the steps mentioned for the application of norms of international law. However, directly inapplicable norms are applied according to the judicature of the Court of the European Union, i.e., according to the place of the act, which implements them, in the legal hierarchy of norms. According to judicature of the Court of the European Union, European Union norms that are of equal legal force with the norms of Latvia have primacy over them.
Theoretical aspects of application of legal norms of international and European Union law in Latvia
Keywords: Juridiskā zinātne